An exploration of the impact of contextual information on the emotion recognition ability of autistic adults. (14th February 2022) - Metcalfe, Dale; McKenzie, Karen; McCarty, Kristofor; Pollet, Thomas V.; Murray, George
Abstract : Studies of non‐autistic individuals and people with an intellectual disability show that contextual information impacts positively on emotion recognition ability, however, this area is not well researched with autistic adults. We investigated this using a static emotion recognition task. Participants completed an emotion recognition task in person or online. In total, 46 autistic participants and 379 non‐autistic participants completed the task. A linear mixed model showed that autistic adults had significantly lower accuracy when identifying emotions across all contexts, compared to control participants, even when contextual information was present. No significant effect of context was found in either group, nor was gender shown to be an influential variable. A supplementary analysis showed that higher scores on the Autism‐Spectrum Quotient led to lower scores on the emotion recognition task; no effect of context was found here either. This research adds to the limited work investigating the influence of contextual factors in emotion recognition in autistic adults. Overall, it shows that context may not aid emotion recognition in this group in the same way as it does for non‐autistic individuals.